Surgeon’s perceptions and preferences in the management of idiopathic macular hole - Devesh Kumawat; Vivek Pravin Dave; Pradeep Venkatesh; Mahesh P Shanmugam; Manish Nagpal; Vishali Gupta; Pramod S Bhende; Naresh Babu; Raja Narayanan; Daraius Shroff; The Macular Hole Survey Study Group (Indian Journal of Ophthalmology)
Purpose: The management of idiopathic macular holes (iMH) has evolved over time with various modifications in surgical approach. The study aimed to survey the surgeons’ preferences in the management of iMH in current times. Design: Cross-sectional descriptive survey. Methods: A 12-item questionnaire addressing the key aspects of iMH management was sent, between October 2022 to November 2022, by personal correspondence to 104 vitreoretinal specialists, actively practicing and performing iMH surgeries at various institutes in India. The responses were gathered till January 2023 and analyzed as per appropriate statistical methods. Results: Ninety-one retina specialists responded to the survey (response rate of 87.5%) with a median annual surgical load of 30 cases (range: 5–150). Most respondents had similar views on patient selection, combined phaco-vitrectomy, internal limiting membrane (ILM) staining, ILM peel initiation and propagation, tamponade, postoperative positioning, and prognostic factors. The preferred approach for peel initiation was “pinch and peel,” but “scrape and peel” was equally recommended for beginners. Most respondents considered iMH >600 microns in size as large and used additional surgical maneuvers for large and failed cases such as ILM flap, large flap, macular detachment, platelet-rich plasma application, and amniotic membrane graft. The three most important visual prognostic factors were duration, preoperative vision, and MH size. Conclusions: The practice of surveyed surgeons performing iMH surgery was uniform in several aspects. There is a need to create consensus on the preferred ILM peel technique among trainee surgeons, revisit the iMH size classification, and standardize the surgical approach as per hole size and characteristics.